(3GdeSFhdjI GdYbOjI Yf aYd GdZjQ (B: s (3OQGSI ebGQfI Hjf GdbGfhfjf GdYQGbi h GdeUQi (B/ s - (3eYGP eMeO jYbhHs; (3LGHQ eMLhH Ydi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3ehVhY HMKfG gh GdeSFhdjI GdYbOjI Yf aYd GdZjQ(B: (3OQGSI ebGQfI Hjf GdbGfhfjf GdYQGbi h GdeUQi(B. (3fXQG dJfhY GdYdGbGJ GdYbOjI abO UGQ ef GdUYH MUQgG(B: (3h JMOjOgG Ydi GdhLg GdObjb(B: (3EP TgO GdYGde JWhQGJ ZjQ eSHhbI Ydi GdUYjO GdGbJUGOi(B: (3h GROGJ JbfjGJ GdJcfhdhLjG h GdGJUGdGJ(B: (3eeG RGO MQcI GdJLGQI(B: (3h EHQGe GdYOjO ef GdYbhO Hjf GdCaQGO(B: (3eG COi HGdeOjf Gdi GddLhA Gdi CTNGU CNQjf(B: (3h GdGSJYGfI Hge(B: (3dJfajP GdJRGeg GdYbOi(B: (3ShGA Ch cd GdYed cdg Edjge Ch LRAG efg(B: (3eeG RGO GdMGLI dfU bGfhfi jbQ HGdeSFhdjI GdYbOjI Yf aYd GdZjQ(B. (3GYJeOJ GdOQGSI NdGd gPg GdOQGSI Ydi efgL JMdjdjG ebGQfG(B: (3h Pdc ef NdGd YQV fUhU GdbGfhfjf GdeOfjjf GdYQGbi h GdeUQi(B: (3eY HjGf ChLg GdGJaGb h GdGNJdGa HjfgeG(B: (3h bO CKQfG SQO MGdGJ JWHjbjI YfO GdcdGe Yf CSGS h TQhW h CKGQ gPg GdeSFhdjI h WQjbI OaYgG h JCejfgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B274-291s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdOGFfs; (3GdZjQ s; (3GdeOjf s; (3GdeSFhdjI GdYbOjIs; (3GdbGfhf GdeUQj hGdYQGbjs; (3CSGS GdeSFhdjIs; (3GdNWC GdeaJQVs; (3GdVeGf GdbGfhfjs; (3GdGdJRGe GdYbOjs; (3fSHjI CKQ GdYbOs; (3GdJYhjVs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs